Marine park visitors’ trade-off among marine ecological attributes in Malaysia. - Arabamiry, Seddigheh; Abdul Rahim, Khalid; Radam, Alias; Khademfar, Mohammad; Yacob, Mohd Rusli (Center for Promoting Ideas, 2013)
The central theme of this study is economic valuation of ecological function values through ecologic al attributes and biophysical indicators; as predicted in the strategic plan 2011-2015 of Department of Marine Park Malaysia(DMPM). So that, visitors of Perhentian Island Marine Park (PIMP) held for these attributes. Applying non -market valuation technique i.e. choice modelling stated preference technique has been pursued to ach ieve this objective. The total collected data consist of 380 Questionn aires that have been completed by visitors through a face-to-face interview in two main islands. Results of Multinomial Logit Models indicated that greatest visitors’ preference for difference attribute levels was respectively for coral cover and water qua lity improvement in the highest level. This e conomic valuation can provide invaluable support to the conservation efforts in direction of maintenance biodiversity to stockholders including policymakers and tour operators.